CONSTRUCTION MANAGEMENT PERFORMANCE ANALYSIS ON PROJECTS SRITANJUNG BANYUWANGI VOCATIONAL SCHOOL PRACTICUM BUILDING - Hari Pranoto; Heru Prasetyo Nugroho (PT. Radja Intercontinental Publishing, 2023)
Management in managing construction work activities is very necessary considering that businesses in the construction sector are currently growing rapidly. Construction management is an organization or individual that is multi-disciplinary. Construction Management can be a business entity which requires human resources who are experts in their respective fields which include POAC (Planning, Organizing, Actuating and Controling) in a systematic and measurable manner. Currently at Sritanjung Vocational School, Banyuwangi Regency, a Practicum Building project is being carried out which is located in the south west part of the school. The research method used in this research is a literature review from various related sources. The data obtained came from filling out questionnaires by respondents involved in the Sritanjung Vocational School Practicum Building project. The questionnaire used was 45 respondents who participated in filling out the questionnaire. The results of the analysis regarding the construction management work system factors in the Sritanjung Vocational School Practicum Building construction project are the most dominant at the implementation stage, while the analysis regarding the actions taken by construction management to control time, cost and quality is the most dominant at the control stage